Integrating Web-Based Resources to Foster Strategic Competence in English Speaking - Jangirova Xadicha Oybek qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: In modern English language education, the development of strategic competence has become an essential component of effective spoken communication. Strategic competence enables learners to overcome linguistic limitations through the use of compensatory strategies such as paraphrasing, circumlocution, fillers, and non-verbal cues. This thesis explores the integration of web-based resources as an effective means of fostering strategic competence in English speaking. The study examines how digital tools, including online discussion platforms, video-based materials, and interactive speaking applications, create authentic communicative environments that encourage spontaneous speech and strategic language use. The research is based on theoretical analysis and practical implementation in English language classrooms. The findings indicate that systematic use of web-based resources enhances students’ communicative confidence, fluency, and ability to maintain interaction despite vocabulary and grammatical gaps. The study concludes that integrating web-based resources into speaking instruction significantly contributes to the development of learners’ strategic competence and overall communicative effectiveness in English.